Protein–Phospholipid Interaction Motifs: A Focus on Phosphatidic Acid - Emeline Tanguy; Nawal Kassas; Nicolas Vitale (Biomolecules, 2018)
Cellular membranes are composed of thousands of different lipids usually maintained within a narrow range of concentrations. In addition to their well-known structural and metabolic roles, signaling functions for many lipids have also emerged over the last two decades. The latter largely depend on the ability of particular classes of lipids to interact specifically with a great variety of proteins and to regulate their localization and activity. Among these lipids, phosphatidic acid (PA) plays a unique role in a large repertoire of cellular activities, most likely in relation to its unique biophysical properties. However, until recently, only incomplete information was available to model the interaction between PA and its protein partners. The development of new liposome-based assays as well as molecular dynamic simulation are now providing novel information. We will review the different factors that have shown to modulate the capacity of PA to interact with specific domains in target proteins.